Unveiling the Growth and Development of Electrical, Computer, and Informatics Engineering Education: A Bibliometric Perspective - Resky Nuralisa Gunawan; Desy Dwi Putri; Ameh Timothy Ojochegbe; Damola Olugbade; Briliant Dwi Zulhaq (Universitas Ahmad Dahlan, 2025)
This study presents a bibliometric analysis of research trends in Electrical, Computer, and Informatics Engineering Education from 2015 to 2023, focusing on the integration of emerging technologies such as AI, IoT, and e-learning platforms. Data was extracted from the Scopus database, and analysis was conducted using co-occurrence analysis and citation network mapping. The study identifies key research themes, such as the shift towards active learning methodologies (e.g., problem-based learning and gamification) and the growing emphasis on technology-driven curricula. Findings show a significant rise in research output, particularly during the COVID-19 pandemic, with IEEE journals dominating publications in the field. The results highlight the transformative role of digital tools in engineering education and the challenges of balancing technological integration with traditional teaching methods. This research offers insights into the evolving landscape of engineering education and provides recommendations for future research directions.